Guest Editors’ Introduction: Everday Religion, Sustainable Environments, and New Directions in Himalayan Studies - Drew, Georgina; Gurung, Ashok (Journal for the Study of Religion, Nature and Culture, 2015)
Georgina Drew and Ashok Gurung introduce this special issue on Everyday Religion, Sustainable Environments, and New Directions in Himalayan Studies.